Rethinking public participation in the smart city - Levenda, Anthony M.; Keough, Noel; Rock, Melanie; Miller, Byron (The Canadian geographer, 2020)
In efforts to become “smart cities,” local governments are adopting various technologies that promise opportunities for increasing participation by expanding access to public comment and deliberation. Scholars and practitioners encounter the problem, however, of defining publics—demarcating who might participate through technology‐enhanced public engagement. We explore two case studies in the city of Calgary that employ technologies to enhance public engagement. We analyzed the cases considering both the definition of publics and the level of citizen participation in areas of participatory budgeting and secondary suites. Our findings suggest that engaging the public is not a straightforward process, and that technology‐enhanced public engagement can often reduce participation towards tokenism. City councillors and planners need to critically confront claims that smart cities necessarily enhance participation. Moving beyond tokenism requires understanding “public” as a plural category. Municipal governments should seek to proactively engage citizens and communities utilizing helpful resources including, but not limited to, digital tools and smart technologies. This would allow planners to keep a “finger on the pulse” of publics' concerns, better identifying and addressing issues of equity and social justice. It is also important to consider how marginalized publics can best be recognized in order to bring their concerns to the fore in decision‐making processes. Repenser la participation du public dans la ville intelligente Dans les efforts qu'ils déploient pour façonner des « villes intelligentes », les gouvernements locaux adoptent diverses technologies qui promettent d'accroître la participation en élargissant l'accès aux consultations et aux délibérations publiques. Les universitaires et les praticiens sont toutefois confrontés au problème de définir les publics cibles, limitant ainsi les catégories de personnes qui pourraient participer à une mobilisation sociale améliorée par la technologie. Dans ce texte, nous analysons deux études de cas à Calgary, cas où l'on utilise les technologies pour améliorer la participation de la population. Nous avons traité ces cas en tenant compte de la définition des publics ainsi que du niveau de participation des citoyens dans les domaines de la budgétisation participative et des logements accessoires. Nos conclusions suggèrent que la mobilisation du public n'est pas un processus simple et que la participation améliorée par la technologie peut souvent diminuer la participation en matière de politique de coopération symbolique. Les conseillers municipaux et les planificateurs doivent aborder de manière critique les allégations selon lesquelles les villes intelligentes améliorent nécessairement la participation. Pour aller au‐delà de la politique de coopération symbolique, il faut envisager le « public » comme une catégorie plurielle. Ainsi, les administrations municipales devraient chercher à mobiliser les citoyens et les communautés en utilisant des ressources pertinentes, y compris et sans s'y limiter, les outils numériques et les technologies intelligentes. Ceci permettrait aux planificateurs « d'être à l'écoute » des préoccupations des publics, de mieux identifier et de mieux s'attaquer aux problèmes d'équité et de justice sociale. Au final, il est également important de tenir compte de la façon dont les populations marginalisés peuvent être mieux reconnus afin de mettre en évidence leurs avis et intérêts dans les processus décisionnels. Key Messages Smart city technologies do not necessarily increase the level of citizen engagement. The idea of a public is a plural, emergent phenomenon that requires careful consideration by planners to enhance equity and participation. Critical perspectives should consider the way publics are formed in relation to smart city technologies.